How to Identify Context on Song Lyrics? A Case on Discourse Analysis on Eminem’s Song Entitled “When I’m Gone” - Betty Jeniari Tambunan; Joint Tondang; Yuliska Gurning; Citra Sani Sinaga; Sumiati Butar-Butar; Herman Herman (Journal of English Language and Education, 2023)
This research aims to analyzing a song lyric entitiled "When l'm gone by eminem", The theme of the song is about Eminem’s relationship between his daughter and his fans.Eminem’s daughter feels disappointed towards his father because Eminem is always busy with his music business and barely spend his time with his family. Descriptive qualitative research was implemented in this research. The data used was a song entitled ‘When I’m Gone’. This song was selected from internet randomly. This research focused to finding the four context, those are physical, epistemic, social context and Linguistics context.This research used the qualitative approach and the lyric as the data.The result show that all of the pragmatics context are found in this song.